THE EFFECT OF APPLYING STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) METHOD ON STUDENTS’ ACHIEVEMENT IN WRITNG DESCRIPTIVE TEXT - Cuna Dwi Mella; Sri Juriaty Ownie (Universitas Negeri Medan, 2013)
This study deals with the applications of Student Teams Achievement Division (STAD)method on students’ achievement in writing descriptive text. The objective of the study wasto find out whether STAD method significantly effected the students’ achievement in writingdescriptive text. This study was conducted to 2012/2013 the seventh grade of SMP N.1 SeiRampah, which consisted of 320 students in eight classes. Fourty students were taken as thesample by using purposive sampling. The sample was divided into two groups. The firstgroup was experimental group, it was taught by applying STAD method in writingdescriptive text, while the second group was control group, that was taught without applyingSTAD method. The instrument that was used in this study was a test. Those test wereconsisted of two test, pre test and post test. The result showed that the realibility of the testwas 0,99. Then, after analyzing the data it was found that the value of t-observed was 3,085with the degree of freedom (df) 38 at the level of significance p(0,05) = 2,002. It means thatt-observed is higher than t-table (3,085 > 2,002). Based on the result, Ha was accepted. Itmeans that STAD method has a significant effect on students’ achievement in writingdescriptive text.